Modern documentary in the age of virtual reality: Deapening engagement with nonfiction storytelling through technological innovation - Pomianowska, Iwona (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
After decades of research, technological development as well as few discouraging setbacks, virtual reality (VR) appears to be on the cusp of its settled adoption. The incorporation of VR technology into the palette of everyday communication media is not only exciting for filmmakers and game designers, but also for every manner of storytellers: documentarians, journalists, educators, scientists – all professions involved in clarifying surrounding us reality and communicating about it. They all discovered that social change can be valuably stimulated by development of new technology – technology that serves in the same time as a classic medium to communicate and spread this news around. Considering the factors enabling us to capture and disseminate “a true story” in a highly captivating, immersive way (which previously has been preserved exclusively for entertainment and commercial productions), we should mention at least 3 crucial elements: technological innovation, psychological evolution of the viewer, application of VR beyond storytelling. The first two factors mutually interact and play off each other in terms of the changing threshold of perceptual tolerance as well as rising needs of the new spectator. The first part of this paper deals with the interdependency of these two elements. Structured conclusions will be enumerated as a practical reference for VR storytelling productions. The second part of the paper will deal with the third element enumerating the most inspiring cases from recent years – eye-openers for instigating social change, adding value and promoting wellbeing via VR technology. The engagement of VR in social change, innovation and nonfiction storytelling introduced the VR technology within the current media palette. It not only changes the nature of storytelling about reality, but fulfills the story that our reality builds.